[Afisz. Incipit] Pracownicy Służby Inwestycyjnej! ... (Gdańsk : [wydawca nieznany], 1955)
Sztrajfa z hasłem propagandowym.
Keywords: Propaganda -- Polska -- 1945-1970 -- druki ulotne; Afisze -- 1945-1990.